Doppler ultrasound evaluation of pattern of venous incompetance and relation with skin changes in varicose vein patients - Pant, HP; Sharma, S; Bhattarai, S; Pandit, SP; Maharjan, D (Journal of College of Medical Sciences-Nepal, 2015)
BACKGROUND Varicosity of lower limb is a common problem in agricultural country like Nepal. Doppler ultrasound is a standard investigation modality for confirmation of diagnosis, evaluation of severity and venous mapping to plan treatment. We aim to find out the epidemiology, common pattern of incompetance, severity assessment by doppler and association of the important doppler variables with skin changes. METHODOLOGY Doppler venous study was done in 56 patients from june 2013 to july 2014. Patients with deep vein thrombosis and peripheral arterial disease were excluded. Altogether 56 patients, 96 limbs were studied. Data was entered in preformed proforma. Doppler study was conducted by senior radiologist with linear probes. Data was entered in SPSS software version 16 and statistical significance was calculated using chi square test. RESULTS Bilateral limb involvement was seen in 40 patients and unilateral in 16 patuents only. Skin related changes were seen in 58 limbs. Saphenofemoral junction incompetance was seen in 79(82.2%) limbs and was most common pattern of incompetance. Overall, superficial veins were involved in 88(91.7%) limbs and deep in 30(31.2%) limbs. Prolonged duration of varicosity (>9 year) (p=0.000), bilateral limb involvement(p=0.024), reflux in deep venous system(p=0.002), larger Greater Saphenous Vein (GSV) size(p=0.003), prolonged duration of reflux(p=0.000) and perforator incompetence (p=0.002) were associated with skin changes. GSV diameter more than 7 mm was associated with reflux significantly (P=0.002). CONCLUSION Superficial vein incompetance is common pattern compared to deep venous system. Sapheno Femoral Junction (SFJ) incompetance is the commonest pattern. Larger caliber of vein, prolonged duration of reflux, reflux in deep venous system and perforator insufficiency are significantly associated with skin changes. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 1-7